Genetic relationships between systemic lupus erythematosus and a positive antinuclear antibody test in the absence of autoimmune disease - Frank Mentch; Nancy J Olsen; Ge Liu; Wei-Qi Wei; Gul Karakoc; Nancy J Cox; Vivian Kawai; Charles Michael Stein; Atlas Khan; Jacy Zanussi; Mingjian Shi; Jonathan Mosley; et al. (Lupus Science and Medicine)
Objective We defined the genetic factors associated with a positive ANA test (ANA+) in the absence of autoimmune disease and tested the association with SLE.Methods Using a case-control design, we performed a genome-wide association study (GWAS) in individuals of European ancestry without an autoimmune disease who had ANA tested as part of clinical care from DNA biobanks linked to de-identified electronic medical records: BioVU and Electronic Medical Records and Genomics. GWAS results were meta-analysed and single nucleotide polymorphism (SNP) heritability was calculated. A polygenic risk score (PRS) for ANA+ and for SLE was constructed and compared in patients with SLE, ANA+ and ANA negative (ANA−) individuals without autoimmune disease and general controls who never had ANA testing performed.Results A total of 7287 individuals of European ancestry were included in the meta-analyses (2169 ANA+ and 5118 ANA−); an SNP upstream of the TSBP1 in the HLA locus (rs1967688) was associated with ANA+ (p=4.84×10−8). SNP heritability for ANA+ was low (h2SNP= 0.04), and the PRS for ANA+ was not significantly different in ANA+ and ANA− individuals. In contrast, the PRS for SLE was significantly higher in SLE compared with ANA+ individuals (p<2.2×10−16) but did not differ among ANA+, ANA− and general control groups (p=0.17).Conclusions ANA+ occurring in the absence of autoimmune disease has a genetic association with the HLA region, but overall heritability is low. In addition, few SLE-associated SNPs were associated with ANA+, and the PRS for SLE was not associated with ANA+, indicating limited genetic overlap.